The dual penal state : the crisis of criminal law in comparative-historical perspective - Dubber, Markus Dirk (Oxford : Oxford University Press, 2018)
This text provides an accessible introduction to the theoretical frameworks of the dual penal state. Taking an issue-led approach, the study locates criminal law in its analytic, comparative, historical, and doctrinal contexts, and aims to stimulate critical reflection beyond the constraints of a particular jurisdiction.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 11, 2018).
Keywords: Criminal law; Criminal law -- History; Criminal justice, Administration of; Criminal justice, Administration of -- History; Law; Laws of specific jurisdictions & specific areas of law